Restoration of intestinal continuity after total colectomy for chronic ulcerative colitis - Mazza, Milton E; Portos, Ruben; Aguiar, Alberto; Muñoz Monteavaro, Cándido; Mescia, Carlos; Kauffman, Pedro; Pérez Fernández, Emilio; Cagno, Carlos (Cirugía del Uruguay, 1975)
In cases of Chronic Ulcerative Colitis, surgery not inevitably imply sacrificing the rectum and definitive ileostomy. A case of a 16 year old male patient with severe chronic ulcerative colitis is described, with surgery practiced in three successive stages ( total colectomy and ileostomy - proctomucosectomy, isolation of distal íleon with ileoproctostomy and proximal ileostomy - Enteroanastomosis), providing re-estableshment of intestinal continuity after total colectomy. The no regression of rectal lesions after colectomy does not always demand sacrificing the organ. Rectal mucosectomy is a practica! and efficient recourse which permits anatomic and functional preservation of the ano-rectum.